THE EFFECT OF BIG BOOKS AS TEACHING MEDIA ON THE SECOND GRADE STUDENTS’ READING COMPREHENSION IN SOUTH BALI - Jayendra, IMS; Nitiasih, PK; Mahayanti, NWS (International Journal of Language and Literature, 2018)
The aim of this study was to investigate whether or not there was any significant effect on the second grade students’ reading comprehension taught by using Big Books as teaching media. The design of this study used post test only control group of quasi experimental research. Therefore the population of this study was second grade students in south Bali. The data were analyzed by using descriptive and inferential statistical analysis. The result of the data analysis showed that students in experimental group performed better than the students in control group. It was proven by the resultthat showed the mean score of the experimental group was 81.59 while the mean score of the control group was 73.64. The result of the t-test also showed the value of t-observed (tobs) was 3.009 and the value of t-critical value (tcv) was 2.018. It shows the value of tobs is higher than the value of tcv. Therefore, it could be concluded that there was significant effect of Big Books as teaching media on the second grade students’ reading comprehension in south Bali.